Nuclear RNA purification by flow cytometry to study nuclear processes in plants - Moro, Belén (STAR Protoc, 2021)
The nature of plant tissues has continuously hampered understanding of the spatio-temporal and subcellular distribution of RNA-guided processes. Here, we describe a universal protocol based on Arabidopsis to investigate subcellular RNA distribution from virtually any plant species using flow cytometry sorting. This protocol includes all necessary control steps to assess the quality of the nuclear RNA purification. Moreover, it can be easily applied to different plant developmental stages, tissues, cell cycle phases, experimental growth conditions, and specific cell type(s). For complete information on the use and execution of this protocol, please refer to Bologna et al. (2018) and de Leone et al. (2020).